Interaksi Antara TikTok Live Streaming, Gaya Hidup dan Inklusif Keuangan dalam Membentuk Perilaku Keuangan Mahasiswa Akuntansi UNWIRA Kupang - Ludgardis M. K. Ca; Genoveva A. Putri; Demetriana D. A. Bau; Yohanes P. Lian (AKUNTANSI 45, 2026)
This study explores the interaction between TikTok Live Streaming, lifestyle, and financial inclusion in shaping the financial behavior of Accounting students at UNWIRA Kupang. The research is grounded in the Behavioral Finance Theory, which posits that financial decisions are driven by psychological biases rather than pure rationality. Using a qualitative descriptive approach, data was collected through triangulation, including In-depth Interviews with 60 students from the 2023-2025 cohort who are active in live commerce. The findings reveal a financial behavior paradox. TikTok Live Streaming proved to be a strong stimulus creating Emotional urgency (flash sales), prompting students to violate their set budgets. A lifestyle influenced by the Fear of Missing Out (FOMO) and the desire for social validation emerged as the main motive for consumptive spending. Furthermore, digital financial inclusion (the ease of e-wallet and QRIS access) acts as a facilitator, removing the pain of paying and accelerating the execution of impulsive purchases. The main conclusion affirms a significant gap between the financial literacy learned by students and their actual practice, demonstrating that behavioral biases are more dominant than Self-control. Educational institutions are recommended to focus on behavior-based financial education.